Pengembangan Bigbook Berbasis Metode Eja Pada Pelajaran Bahasa Indonesia Untuk Meningkatkan Minat Belajar Siswa Di Sekolah Dasar - Aprila Nabila; Wahyu Satria; Renni Ramadhani (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
The development of the Big Book based on the spelling method in Indonesian language lessons to increase students' interest in learning in elementary schools is based on the understanding that high interest in learning plays a crucial role in achieving learning. The aim of this research is to test the effectiveness of bigbook media based on the spelling method based on learning interest in elementary school students. The method used in this study uses a library research method or approach. Library research (library research) is research in which data collection is carried out by collecting data from various literature. This method is based on the previous page list which is often used initially, but this is also available, but the Ledger is available on both sides of the screen and visually which means it is in the right place. Just the same, a lot of people who have nothing to do with anyone else want to know what to do, but what's going on here.